The Influence of Incentives and Satisfaction on Driver Performance - Budhi Satriawan; Puti Harissa (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
The development of start-up businesses in Indonesia has become a challenge for other transportation service providers that operate conventionally. The last decade has provided the most important breakthrough in the form of online transportation services. The presence of various online transportation applications has received a positive response from the public because it provides convenience in getting transportation quickly, cheaply, safely, and comfortably. However, problems arise when drivers complain about the incentives given especially by Grab in the city of Bandung. The purpose of the study was to examine how much influence the provision of incentives and job satisfaction had on the performance of online motorcycle taxi drivers in the city of Bandung. The statistical technique used in this study uses multiple linear regression analysis. Primary data were obtained from respondents as many as 91 Grab drivers in the city of Bandung who are members of the Grabbike Bandung community. While secondary data is obtained through notes and publications. The results showed that the variables of providing incentives and job satisfaction had a significant effect on driver performance. Based on the test results, the coefficient of determination shows that the effect of the three independent variables on the dependent variable is 67.2%. While the remaining 32.8% is influenced by other variables not examined. This research is proposed for the existence of gaps or problems experienced by online motorcycle taxi drivers regarding the provision of incentives that are deemed inadequate so that it reduces the performance of drivers, especially online motorcycle taxi drivers in the city of Bandung.